Equal pay in W.A. - Preston, Alison (Curtin University of Technology, 2000)
Notwithstanding more than 30 years of equal pay within Australia,females continue to earn significantly less than their malecounterparts. Recent data indicates that nationally the adjustedgender wage gap in hourly earnings in the full-time labour market isaround 10.5 per cent. In Western Australia (WA) the equivalent gapis significantly higher, equal to 18.5 per cent. Previous researchexamining the extent of gender wage inequality within WA has beencriticised for failing to adequately control for gender differences inhours of work in the full-time labour market in WA. This paper revisitsthe issue of female wage inequality in WA using alternative data sets.The results confirm the robustness of previous studies and furtherhighlight the large and significant wage gap within the state. Theresults should make interesting reading for those associated with thedevelopment of policies to achieve equal pay in WA.